JESSE’S PSYCHOSOCIAL DEVELOPMENT IN THE NOVEL MY SISTER KEEPER BY JODI PICOULT (2004) - Lilik Kosiaroh; Dyah Sunggingwati; Chris Asanti (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2017)
ABSTRACT This research identified about the stages of Jesse’s psychosocial development and the kind of factors that changed Jesse as a dynamic character. The method used descriptive qualitative, where the researcher described the stages of psychosocial development views of Jesse character and then tried to find out about the familial conflict that occurred on him. First was early childhood, Jesse was two years old and his personality still good. Second was play age. In this stage, Jesse changed his personality, because of the different treatment by his parents that he was yelled by his parents. Third was school age, Jesse was five until eleven years old. He did some rebellion to get attention from his parents, for example; revoked his teeth by using a fork and tried to suicide. Fourth was adolescent, it was the climax of Jesse’s character, between the age of twelve to eighteen years old; Jesse performed some bad behaviors or risky behaviors. He did smoking, consuming drugs, stealing, and having obsession with fire. He did all of them, because he depressed with many conflict in his family. In the last stage was middle adulthood, Jesse was taken care again by his parents. Keywords:  character, psychosocial, psychosocial development, familial conflict  ABSTRAK Penelitian ini mengidentifikasi tahap dari perkembangan psikososial Jesse dan jenis dari faktor yang mengubah jesse menjadi karakter dinamik. Penelitian ini menggunakan metode deskripsi kualitatif, dimana peneliti mendeskripsikan tahap dari perkembangan psikologi Jesse dan mencoba mencari masalah yang mengganggunya. Pertama adalah tahap anak usia dini, Jesse berumur 2 tahun dan psikologinya tetap baik. Kedua adalah tahap bermain. Pada tahap ini Jesse mengubah personalitinya, karena perubahan perlakuan yang diberikan orangtuanya yang membentaknya. Ketiga adalah tahap sekolah, Jesse berumur 5 sampai 11 tahun. Jesse melakukan banyak pemberontakan untuk mendapat perhatian dari orangtuanya, contohnya; ia mencabut giginya menggunakan garpu. Keempat adalah tahap remaja, ini adalah puncak dari permasalahan Jesse diumur 12 -18 tahun. Jesse menunjukkan beberapa kesalahan dan kerusakan dirinya. Dia merokok, mengonsumsi narkoba, mencuri dan terobsesi dengan api. Ia melakukan itu semua, karena ia depresi dengan semua masalah dalam keluarganya. Pada tahap terakhir Jesse kembali diberi perhatian oleh orangtuanya.  Kata Kunci : karakter, psikososial, perkembangan psikososial, masalah keluarga